Principles of the administrative procedure code and their contributions to accountability: the Portuguese case - Lima, Débora Reis Leal de (2021)
Objective: The objective of this study is to analyse the contributions that the general principles established in the Portuguese Code of Administrative Procedure (Decree-Law no. 4/2015, January 7) have made to the exercise of accountability. Method: Research was conducted using the qualitative method through bibliographic and documental research. Originality/Relevance: Approval of the current Code of Administrative Procedure (Decree-Law no. 4/2015, January 7) brought important innovations in relation to the previous text, especially in its general principles of administrative activity. Among the changes, there is particular mention of the need for efficiency in Public Administration, its commitment to the accountability of its actions and ensuring popular participation. The study analyzed whether the inclusion of these principles strengthens pursuance of the Democratic State of Law, providing a favorable environment for the demands of accountability, as intended by the diploma. Results: The analysis carried out shows that the current Code of Administrative Procedure acts in close proximity to constitutional values and the dimensions involving the concept of accountability, being in thesis an instrument to guarantee democratic legitimation. Theoretical/Methodological contributions: The research contributes to discussion of the theme in Public Administration and to broadening the discussion in the literature, and particularly in the Portuguese legal system, whether the principles of the CAP contribute to accountability in public entities, given the new challenges presented by the growing complexity of modern societies and new visions of Public Administration.